The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1523/jneurosci.4452-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Spinal μ-Opioid Receptor-Expressing Dorsal Horn Neurons: Role in Nociception and Morphine Antinociception

Abstract: The role of spinal cord -opioid receptor (MOR)-expressing dorsal horn neurons in nociception and morphine analgesia is incompletely understood. Using intrathecal dermorphin-saporin (Derm-sap) to selectively destroy MOR-expressing dorsal horn neurons, we sought to determine the role of these neurons in (1) normal baseline reflex nocifensive responses to noxious thermal stimulation (hotplate, tail flick) and to persistent noxious chemical stimulation (formalin) and (2) the antinociceptive activity of intrathecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 48 publications
(66 reference statements)
5
37
0
Order By: Relevance
“…These areas also express opioid receptors, which localize to pre-synaptic terminals of primary sensory neurons as well as to their postsynaptic targets in laminae I and II (Kline and Wiley, 2008). In the present study, we found that MOR-IR neurons in the dorsal horn frequently expressed ER α .…”
Section: Discussionmentioning
confidence: 99%
“…These areas also express opioid receptors, which localize to pre-synaptic terminals of primary sensory neurons as well as to their postsynaptic targets in laminae I and II (Kline and Wiley, 2008). In the present study, we found that MOR-IR neurons in the dorsal horn frequently expressed ER α .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that in females, the PAG is not the primary anatomical substrate for the analgesic effects of morphine. Both the RVM (Porreca et al ., 2001; Burgess et al ., 2002) and the dorsal horn of the spinal cord (Kline & Wiley, 2008) contribute to morphine antihyperalgesia and perhaps these sites are more critical in females. In support, we have recently reported no differences in MOR expression within the lumbosacral spinal cord and similarly, no differences in ED 50 values for morphine when administered intrathecally (Ji et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while vlPAG MOR obviously contributes to the effects of exogenous morphine, its reduction does not appear to alter endogenous pain modulation during inflammatory hyperalgesia suggesting that other pain inhibiting regions, including the RVM and spinal cord are involved. In support, previous studies have reported that DermSAP lesions of MOR-expressing neurons in the RVM (Porreca et al ., 2001; Burgess et al ., 2002) and dorsal horn neurons (Kline & Wiley, 2008) attenuate hyperalgesia in male rats. Together, these data indicate that the RVM and the dorsal horn of the spinal cord, but not the PAG, are essential for driving descending facilitation (Terayama et al ., 2000; Ren & Dubner, 2002; Dubner & Ren, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, substance P, which is coreleased from the central terminals, facilitates the relief of the Mg 21 block in the NMDA receptor, leading to the enhancement of NMDA receptor signaling (Khasabov et al, 2002;Suzuki et al, 2003). Other postsynaptic GPCRs that modulate NMDA receptors include metabotropic glutamate (D'Mello and Dickenson, 2008), CGRP (Yan and Yu, 2004), and m-opioid receptors (Gracy et al, 1997;Kline and Wiley, 2008). These receptors are known to couple to G q , G s , or G i proteins.…”
Section: Inhibition Of Inflammatory Pain By Mrgc Receptorsmentioning
confidence: 99%